Radar trends to watch February 2025 : developments in web, virtual reality, robotics, and more - Loukides, Michael Kosta (O'Reilly Media, Inc., 2025)
Read about the latest developments on O'Reilly Media's Radar.
Includes bibliographical references
Keywords: Artificial intelligence -- Technological innovations; Computer programming -- Technological innovations; Computer security -- Technological innovations; World Wide Web -- Technological innovations; Virtual reality -- Technological innovations; Quantum computing -- Technological innovations; Robotics -- Technological innovations; Biology -- Technological innovations; Information technology -- Technological innovations; Intelligence artificielle; Innovations; Programmation (Informatique); Innovations; Sécurité informatique; Innovations; Web; Innovations; Informatique quantique; Innovations; Robotique; Innovations; Biologie; Innovations; Technologies de l'information et de la communication